Examining the Level of Satisfaction of the Elderly Referring to Health Care Centers with Health Services Treatment of the Integrated Care Program for the Elderly in Fars Province - Saffari, Masoumeh; Ansarifard, Mahin; Rabet, Zahra; Karam pour, Mino; Shabanzadeh, Raha (Shahroud Journal of Medical Sciences, 2024)
Background: The phenomenon of population aging following the increase in life expectancy and decrease in mortality in societies is a sign of the progress and development of countries, but if societies do not have the necessary preparation to deal with the needs of the elderly, especially their health needs, they will face serious challenges. This study aimed to investigate the level of satisfaction of elderly people who refer to health care centers with integrated care services for the elderly in Fars province.Methods: The present study was conducted in a descriptive-analytical manner on 1500 elderly people who were referred to health care centers covered by Shiraz University of Medical Sciences using a simple random method. The data was collected using a checklist of demographic information and a researcher-made questionnaire. After collecting the data, it was entered into SPSS 18 and analyzed with descriptive and analytical statistics.Results: The results showed that out of 1500 seniors who were referred, most of them were in the age group between 60-70 years old with 715 (47.6%), female gender 972 (64.8%), married 651 (85.9%), education level (53.7%) was at the elementary level and referred to urban centers with (68%) 1020 cases, and most of the satisfaction was related to the service providers (personnel) and the least satisfaction was related to the process of providing health services. Also, the elderly with a history of receiving services were far more satisfied than those who visited for the first time. The most dissatisfaction was with the facilities and equipment of health service delivery units and the duration of the service delivery process.Conclusions: Despite the high satisfaction of the elderly, it is necessary to pay attention to the continuous improvement of the level and quality of health services for the elderly. According to the findings of the study, the need to provide facilities and modify the process of providing health services for the elderly according to their special needs, paying more attention to the empowerment of integrated care providers for the elderly as basic solutions to increase the satisfaction level of the elderly more than it is revealed.